AMERICAN MYSTICISM AND FEMINISM IN CASSANDRA CLARE'S CLOCKWORK ANGEL: A POSTMODERNIST FICTION - Asih Putri Wardhani; Hat Pujiati; Ikwan Setiawan (Haluan Sastra Budaya, 2020)
Postmodern as a stage of civilization after traditional and modern tends to accommodate the two previous stages with its newness. This article studies the postmodern strategies depicted in Cassandra Clare’s The Infernal Defices: Clockwork Angel in Brian McHale’s perspective which emphasize his idea of postmodernist fiction based on ontological dominant while the modernist is epistemological dominant. How the ontological is constructed in the novel become the aims to reveal in this article. Through Hrusovski’s three dimensional semiotics concept that is developed by McHale, this article starts the analysis of ontological landscape from words, worlds and construction of the novel. The result is that heterocosmos are built in intertextualzones  based on pre-Victorian, Victorian and post-Victorian poems which become the epigraph in every chapter of the novel using interpolation and superimposition strategies.Beyond the ontological landscape, this novel shows the spirit of American mysticism and feminism.